Assessment of the ecological state of surface waters of the Luga River, in the town of Volodymyr, by macrophytes - Tsos, Oksana; Radzii, Volodymyr; Kocun, Larisa; Sukhomlin, Kateryna; Melnyk, Oleksandr (Видавництво Університету природничих наук у Любліні, 2024)
The objectives of our research were an ecological assessment of the quality of the Luga River water in the town of Volodymyr (Volyn region, Ukraine) by physico-chemical and phyto-indicative parameters, analysis of the species composition of the flora of aquatic and coastal aquatic plants by ecotypes, identification of protected species and indicator species. The studies were made during the 2022-2023 growing season at four test sites within the town of Volodymyr. According to the results of field floristic studies of selected test sections of the Luga River in Volodymyr, 25 species of aquatic and coastal-aquatic plants were found, belonging to the division of Magnoliophyta, two classes (Magnoliopsida and Liliopsida), and include sixteen families and twenty-two genera. The most represented class Liliopsida includes 16 species (64%) belonging to 13 genera and 8 families. The class Magnoliopsida consists of 9 species belonging to 9 genera and 8 families. During the research, 13 types of macrophyte indicators were found at test site No. 1 (Old Cathedral), 19 indicator species at test site No. 2 (Hydrological station), eight species at test site No. 3 (Lyceum boarding school), and eight species on site No. 4 (Shistivsky Bridge). The Macrophyte Index for Rivers (MIR) of the Luga River in the town of Volodymyr varies generally from 30.75 to 36.71, which corresponds to water quality Class III, satisfactory ecological condition; except at test site No. 2 where water quality is Class II, good ecological condition.
Keywords: ecological assessment of rivers; macrophyte index MIR; the Luga river